Simultaneous recovery of ammonium sulfate and ice from aqueous solution using eutectic freeze crystallization process - W.H.T., Ting; Shanti Faridah, Salleh; Noraziah, Abdul Wahab; Mohd Farid, Atan; A.A., Abdul Raman; W.K., Ting; S.L., Kong; L.S., Lam; Ivy Ai Wei, Tan (Elsevier B.V., 2025)
This study investigated the feasibility of eutectic freeze crystallization (EFC) process for ammonium sulfate (AS) salt recovery from 41 wt% AS solution. The EFC experiments were conducted using a 1 L double-jacketed crystallizer coupled with a recirculating chiller under varying freezing time, seed mass and seed size. The EFC process demonstrated successful AS salt recovery and water purification with the highest ice purity attained at 96.28 %. The construction of a binary AS-water phase diagram allowed the determination of the eutectic tem perature, which was found to be − 19.06 ◦C at 40 wt% of AS solution. The results indicated that the increase in freezing time enhanced the AS nucleation rate, growth rate, yield and mean product crystal size. The intro duction of seeding not only provided well-controlled crystal nucleation and growth during EFC process, but also promoted the formation of larger, well-structured crystals and reduced agglomeration. Overall, the EFC process is a viable and promising option for recovering AS from wastewater, which offers high potential towards achieving zero liquid discharge goal, i.e. a sustainable and efficient approach in managing industrial effluent rich in ammonium and sulfate contaminants.